Rethinking sustainability: questioning old perspectives and developing new ones - Ramos, Tomás B. (2021)
The concept of sustainability is still progressing, being complex and contested, and is therefore under continuous discussion and research. This special volume comprises 29 articles exploring recent developments of sustainability concepts, approaches, strategies, policies, and practices, as well as their roles and applicability in different geographic, socio-cultural and economic contexts. The majority of the articles were presented at the 22nd conference of the International Sustainable Development Research Society (ISDRS), held in Lisbon, Portugal, in July 2016. The articles address six overarching themes: i) global perspectives on sustainability challenges, policies and models; ii) the next frontiers of sustainability for corporations, iii) integration of non-traditional aspects and new forms of knowledge in sustainability research, iv) planning for sustainable development and sustainable cities, v) (higher) education for sustainable development and vi) human resources and sustainability. A summary of each article is given in this editorial, showing the diversity of themes, from theoretical and practical perspectives, and the broad range of different methods and research formats. The research presented in the articles was carried out in more than 17 countries on five continents. Notwithstanding the many efforts around rethinking sustainability research and practices, there are still many challenges to face and further opportunities for research on the topic.